Plantation Indian women: A sociological study of Indian women in Ladang Cha’ah, Johore / Karthyeni Sridaran - Karthyeni , Sridaran (1987)
This study examines the socio-economic status of Indian women in the plantation. Utilizing a sociological approach, the research was conducted among 45 Indian women respondents in Ladang Cha'ah, an oil palm plantation in the state of Johore in Peninsular Malaysia. The thesis is present ed in five chapters. The first chapter is an introductory chapter which explains the objective of the research and the sociological methods used to obtain data on the subject of study. It also discusses the theoretical framework of the research and the traditional image of women in the Indian culture. The second chapter gives a brief historical perspective of the plantation community but mainly focuses on the place of resear ch with a general description of the setting. It also discusses the occupational structure, income and expenditure patterns within the estate. The main part of chapter three is a discussion on the position of women in relation to work. This is divided into estate work and domestic work where the status of women is examined with regards to her economic and social functions within and outside the home. Attention is also paid to leisure activities among these plantation workers. Chapter four begins with an introduction to the importance of education with regards to social status and continues with an analysis of the educational attainment among the women respondents. It further explains the factors affecting educational achievements among these plantation women. Finally, chapter five gives a general analysis of hte status of Indian women in the plantation in line with the theoretical perspective and concludes with a few suggestions on how to improve the socio-economic status of these women in the plantations.